(untitled) (Bangladesh Veterinarian, 2011)
Glutathione (GSH) 0 (control), 2, 4 and 8 mM was used in the preservation of chilled goat semen. Treated and control samples were kept at 4 – 5°C up to seven days. Sperm motility and acrosome abnormality were assessed daily under phase contrast microscope. The sperm motility was significantly (P<0.01) higher in the semen treated with 8 mM GSH. Optimum sperm motility (≥50%) for artificial insemination was retained for three days with 2 and 4 mM GSH and up to four days with 8 mM GSH. Acrosomal damage was significantly (P<0.01) reduced to ≤ 1.0% after addition of 8 mM GSH. It is suggested that GSH may be used as an antioxidant for better preservation of goat semen for artificial insemination. DOI: 10.3329/bvet.v27i2.7554 Bangl. vet. 2010. Vol. 27, No. 2, 46 – 55